1994
DOI: 10.1007/bf00218911
|View full text |Cite
|
Sign up to set email alerts
|

Presence of an expressed ?-tubulin gene (TUBB) in the HLA class I region may provide the genetic basis for HLA-linked microtubule dysfunction

Abstract: Abstract. An expressed I]-tubulin gene (TUBB) has previously been localized to chromosome region 6pter-p21 in man. By using a panel of deletion mutant cell lines and radiation-reduced hybrids containing fragments of chromosome 6, the TUBB locus could be mapped to the HLA class I region at 6p21.3. A long range restriction map including TUBB and several HLA class I genes was then generated by rotating field gel electrophoresis. The results show that TUBB maps to a segment 170-370 kb telomeric of HLA-C. This loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Whilst the P3B locus does not itself encode a protein, a novel member of a multiple copy gene family which codes for polypeptide sequences distinct from class I has previously been mapped in close proximity to it [21]. Recently, a gene coding for a putative GTPbinding protein HSR1 as well as tubulin-B have also mapped close to HLA-E and the P3B locus [22,23]. The HLA-E locus is less than 100 kb telomeric of P3B ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Whilst the P3B locus does not itself encode a protein, a novel member of a multiple copy gene family which codes for polypeptide sequences distinct from class I has previously been mapped in close proximity to it [21]. Recently, a gene coding for a putative GTPbinding protein HSR1 as well as tubulin-B have also mapped close to HLA-E and the P3B locus [22,23]. The HLA-E locus is less than 100 kb telomeric of P3B ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have demonstrated that tubulin is a target site for a number of antitumor drugs, among which β-tubulin has seven species of isomers and its coding genes are located in 6p21.3 (1). According to the combined detection with isoelectric focusing and mass spectrometry, β-tubulin-III has been recognized as the only marker with a resistance to a microtubule drug among the seven species of isomers.…”
Section: Introductionmentioning
confidence: 99%
“…Third, there is the case of chromosome 7 uniparental disomy and other chromosomal anomalies with KS-like symptoms, summarized in the letter by Pan et al (1998). PCD candidates on other chromosomes include the following: (1) the HLA region of chromosome 6p, containing the btubulin gene (TUBB) (Volz et al 1994), although limited data reported elsewhere (Gasparini et al 1994) did not support the motylin gene (MLN), also residing in this region, as being a candidate for involvement in PCD etiology; (2) chromosome 14q32, containing the gene for echinoderm microtubule-associated protein (EMAP), a candidate for Usher syndrome type 1A (the USH1A gene) (these patients exhibit, in the axonemes of their respiratory cilia ultrastructural defects similar to those in PCD) (Bonneau et al 1993;Eudy et al 1997); (3) the dynein heavy-chain gene located on 14qter (Narayan et al 1994a); and (4) numerous other dynein, nexin, and other microtubule-related genes rapidly accumulating in the genomics databases. Many genes have been implicated recently in the control of the left-right asymmetry of body development such as that observed in KS (Overbeek 1997;Srivastava 1997;Wood 1997;Levin and Mercola 1998).…”
Section: Figurementioning
confidence: 99%